Health education for nurses on the risks of social stigma and injury in the elderly - Anung Ahadi Pradana; Lindesi Yanti; Alfunnafi' Fahrul Rizzal; Ni Luh Putu Dian Yunita Sari; Aris Teguh Hidayat; Sri Ayu Rahayu S. Paneo (Universitas Muhammadiyah Magelang, 2022)
The rise in the elderly population in recent years may increase the risk of societal stigma associated with aging. In addition to causing frailty in the elderly, the negative stigma of aging that has emerged in society has the potential to cause material and non-material losses. It is possible to prevent this by providing proper health education to health care workers. The purpose of implementing this community service program is to improve nurses' understanding of the risks of negative stigma associated with aging and injury in the elderly. 313 nurses from nine provinces participated in this community service activity, which was conducted entirely online. After the team educated the participants on ten main topics, it was discovered that providing health education about the risks of negative stigma about aging and the risk of injury to the elderly had positive benefits for nurses.